Tibetan Printing: Comparison, Continuities, and Change - Diemberger, Hildegard; Ehrhard, Franz-Karl; Kornicki, Peter (Brill's Tibetan Studies Library, 2016)
Tibetan Printing: Comparisons, Continuities and Change is the first publication that brings together leading experts from different disciplines to discuss the introduction of printing in Tibetan societies in the context of Asian book culture. Readership: All interested in Tibetan Studies, in Asian Book Cultures and the history of printing as well as in interdisciplinary approaches to the study of books as artefacts.